Solar to Chemical Energy Conversion Theory and Application - Sugiyama, Masakazu; Fujii, Katsushi; Nakamura, Shinichiro (Lecture Notes in Energy, 2016)
This book explains the conversion of solar energy to chemical energy and its storage. It covers the basic background; interface modeling at the reacting surface; energy conversion with chemical, electrochemical and photoelectrochemical approaches and energy conversion using applied photosynthesis. The important concepts for converting solar to chemical energy are based on an understanding of the reactions' equilibrium and non-equilibrium conditions. Since the energy conversion is essentially the transfer of free energy, the process are explained in the context of thermodynamics.